EFEKTIFITAS PENYULUHANÂ DENGAN MULTIMEDIA SEBAGAI MEDIA UNTUK Â PENCEGAHAN TERJADINYA Â FLUOR ALBUS PADA REMAJA PUTRI - Roifah, Ifa (JURNAL KEPERAWATAN SEHAT, 2016)
Health program in school with UKS is good program, because teenagers is the biggest group in the world, school is formal institution and easy to make in group of health, health promotion in teenagers will be more efficient and effective to make a good helath behavior. Multimedia is combination from two or more media input or out put. This media can organize as audio (sound and music), animation, video, text, graphic, and picture.The purpose of this research is to know the influence of education on genetalia hygiene using multimedia to whitish prevention fluor albus of young women at class VIII. The research design used, namely pre-recorded one-design of experiments with group pre-post test design. Sampling in this study using random sampling techniques systematic. The population in this research as much as 61 young women at class VIII, there are 30 people who become the respondents. The data take by quisionaire. McNemar test resulted that there is an impact health education with multimedia to prevent fluor albus. Multimedia effective to increase knowledge of teenagers because multimedia viewing data in audio, animation, video, and others because that it can make easier and interest to understanding.Keywords:Leucorrhoea, Hygiene Genitalia, Multimedia.